-4+3f=2f

Simple and best practice solution for -4+3f=2f equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -4+3f=2f equation:


Simplifying
-4 + 3f = 2f

Solving
-4 + 3f = 2f

Solving for variable 'f'.

Move all terms containing f to the left, all other terms to the right.

Add '-2f' to each side of the equation.
-4 + 3f + -2f = 2f + -2f

Combine like terms: 3f + -2f = 1f
-4 + 1f = 2f + -2f

Combine like terms: 2f + -2f = 0
-4 + 1f = 0

Add '4' to each side of the equation.
-4 + 4 + 1f = 0 + 4

Combine like terms: -4 + 4 = 0
0 + 1f = 0 + 4
1f = 0 + 4

Combine like terms: 0 + 4 = 4
1f = 4

Divide each side by '1'.
f = 4

Simplifying
f = 4

See similar equations:

| 6(6x+1)=9(4x-3)+5 | | -7+6(-8n+8)=(-2+5)+7 | | C+2c+c=20 | | 7+19t-2=9t+107-7t | | x+(3)=-7 | | 5x*2-1+2x*2+x+5=0 | | 3(-3y-3)=-9+23 | | 20c-15c=10 | | 11=7x+1-5x | | 110-4x=170-8x | | -5a-4a+2a=14 | | -22=4x-6x-2 | | 2.7+10m=6.35 | | 9-2x=3(2x-5) | | 3(x-5)+2=7(2-x)+1 | | 4r+16=4r-32 | | 6-x-1=6-[x+1] | | 10+6y-6y=7 | | 2n+2n-4n+n+2n=9 | | -7x-7+2x=-62 | | 16a^2+4a-6=0 | | x*2+3x+5=x*2-x+4 | | 3*x+(x-10)=200 | | 10=-2x-x+7 | | y=100(0.78)3x | | 10(2y+2)-y=2(8y-2) | | 0.88+0.16(10-x)=0.40x | | 6-x-1=6-(x+1) | | 7-4x-2x=-35 | | (-4x)+(-3x)+x= | | 5c-1=34 | | -(-6y-3z+6)= |

Equations solver categories